The Effectiveness Of Using Learning Media To Increase Knowledge And Preventive Measures Of Diabetic Foot Ulcers In Patients With Diabetes Mellitus - Lestari Lestari; Suriani Br. Ginting; Nani Zulfikar; Siti Hasanah Siregar (Asosiasi Guru dan Dosen Seluruh Indonesia, 2022)
Background : Diabetic foot ulcer is one of the complications of DM's disease. Prevention of diabetic foot ulcers can be done by providing health education to improve the knowledge, attitudes, or actions of patients with diabetes mellitus but it is very necessary to provide a health education in order to be able to understand and able to do it. In fact diabetic ulcer numbers are increasing. It is necessary to increase the method and media delivery of the health education. Objective: The literature of this review aims to be to know the effectiveness of the use of media learning towards increased knowledge and preventive measures of diabetic foot ulcers as well as finding similarities, differences, advantages and disadvantages of the journals in review. Methods: This study uses review literature designs obtained from Google Scholar sources. The key word in this review literature search is the prevention of diabetic foot ulcers with dependent variable use of learning media and independent variables of knowledge and action. Results: Out of 5 studies gained 3 national journals and 2 international journals with the result that health education using the media has a significant influence on knowledge, attitude, and practice.